A Collaborative Study of Proposed European Pharmacopoeia Reference Preparations of Low Molecular Mass Heparin - Gray, E; Heath, A B; Mulloy, B; Spiese, J-M; Barrowcliffe, T W (Thrombosis and Haemostasis, 1995)
A European collaborative study, in which 16 laboratories participated, was carried out to assess the performance of the European Pharmacopoeia (EP) monograph methods for anticoagulant activities (anti-Xa and anti-IIa assays) of low molecular mass (EMM) heparin and to assess the suitability of six candidate materials as the EP working standard for LMM heparin. There was good interlaboratory agreement for both types of assays as indicated by most gcv’s being less than 10%, indicating acceptable performance of the EP assay methods. All the candidate preparations gave dose-response curves parallel to the 1st International Standard for Low Molecular Weight heparin and to each other. All preparations, possibly with the exception of E and F, gave similar performance as measured by interlaboratory agreement and would be suitable as working standards. Based on these data, preparations A, B, C and D have been established by the EP as official EP Biological Reference Preparations and they will be issued as successive batches.